THE EFFECT OF ORGANIZATIONAL COMMITMENT AND CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE (A CASE STUDY OF THE ASSOCIATION OF PRIVATE UNIVERSITIES REGION IXA CENTRAL SULAWESI (APTISI IXA CENTRAL SULAWE - Konduwes, Fachryh; Thahir, Harifuddin; Asngadi, Asngadi (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to determine and to analyze: The effect of organizational commitment and culture on organizational citizenship behavior through job satisfaction as an intervening variable in the work area of ​​the Association of Private Universities Region IXa Central Sulawesi (APTISI IXa Central Sulawesi). The research population was 1886 lecturers at private universities in the working area of ​​APTISI IXa, Central Sulawesi. Seeing the large population, this research used the Probability Sampling technique with the Slovin formula to obtain Proportional Random Sampling as many as 330 research samples. The results reveal that Organizational Commitment had a significant effect on Organizational Citizenship Behavior, with a P Value of 0.000 <0.05. Organizational Culture has no significant effect on Organizational Citizenship Behavior, with a P Value of 0.066 > 0.05. Organizational Commitment has a significant effect on Job Satisfaction, with a P Value of 0.000 <0.05. Organizational Culture has a significant effect on Job Satisfaction, with a P Value of 0.000 <0.05. Organizational Commitment to Organizational Citizenship Behavior, with a P Value of 0.000 <0.05. Organizational Commitment through Job Satisfaction has an effect on Organizational Citizenship Behavior, with a P Value of 0.00001617 <0.05. Organizational Culture through job satisfaction has no effect on organizational citizenship behavior, with a P value of 0.76895864 <0.05. Keywords: Organizational Commitment, Organizational Culture, Organizational Citizenship Behavior and Job Satisfaction